Pengaruh Arus Kas Operasi Dan Laba Akuntansi Terhadap Tingkat Keuntungan Saham - Nurlailatul Laifah, Ika; Adi Rahardjo, Kusuma; Supriadi, Imam; Muchran Noor, Gusti (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This research aims to examine the influence of Operating Cash Flow and Accounting Profit on the level of stock profits because in reality there are several differences between the relationship between each variable and the level of stock profits for consideration by potential investors before investing in shares. This research uses a quantitative approach with secondary data as a source of information. The theory used is signal theory. The independent variables in this research are Operating Cash Flow and Accounting Profit, while the dependent variable in this research is the stock profit rate. The population in this study was 99 companies. This research uses a purposive sampling technique with a sample of 31 companies and produces observation sample data of 93 companies in the period 2020 – 2022. The analysis technique used is Statistical Product and Service Solutions (SPSS) version 25. The results of this research show that Operating Cash Flow has an effect positive effect on stock profit levels, while accounting profits have a negative effect on stock profit levels. Simultaneously, these two independent variables influence the level of stock profits. It is hoped that potential investors and issuers will always pay attention to liquidity as one of the highlights when considering stock investment.